PROFILING PELAKU PENCABULAN ANAK: STUDI KASUS DI KABUPATEN KAMPAR RIAU - Andi Wardana; Ivan Muhammad Agung; Adri Murni (UIN Sunan Kalijaga, 2013)
One of the criminal offense in Indonesia to be a problem for parents is child sexual abuse. This study aims to determine the profle of perpetrators of sexual abuse on child. The approach used is a qualitative approach using case studies. Methods of data collection using interviews and documentation. Subjects were the perpetrators of child abuse, amounting to three people. The result showed a number of themes in profling, which is characteristic of the perpetrator and the victim, the perpetrator and victim relationships, order a criminal offense, victim selection, controlling the victim, perpetrator motivation and mode. In general it can be concluded that the perpetrator is someone close to the victim, carried himself and planned, motivation to satisfy sexual urges, use agreements and threats to control the victim.